Students' Interest in Using the Quick Response Code Indonesian Standard Payment System for Vocational Education Program Students Serang Raya University - Radho, Muhamad; Lestari, Novia Indah (Universitas Serang Raya, 2022)
The millennial generation is a generation that demands all aspects of their lives, including transactions. The cashless lifestyle is increasingly mushrooming in the midst of Indonesian society, especially the millennial generation. This study aims to determine the interest of students in using the Quick Response Code Indonesian Standart (QRIS) payment system for UNSERA Vocational Education Program students. The object of this study is students of the UNSERA Vocational Education Program using quantitative research methods and this type of research uses descriptive statistics. The population in this study was 103 people, and a sample of 82 people was taken using random sampling techniques. Analyze data by using descriptive statistics. In this study, the quantitative analysis method used was analysis using Microsoft Excel. The results of the research that the majority of vocational education program students have an interest in using QRIS payment technology such as Gopay, Shopeepay, Dana, Ovo, etc. Because in its use QRIS is very easy and safe in making payments through any merchant in one QR Code and this is the biggest financial breakthrough in Indonesia today. The benefits of this research for the millennial generation are expected to be able to understand digital payments using standardized payment QR codes, as well as become endorsers in voicing QRIS to the wider community.